2020
DOI: 10.1021/acs.molpharmaceut.0c00268
|View full text |Cite
|
Sign up to set email alerts
|

Atomic-Level Drug Substance and Polymer Interaction in Posaconazole Amorphous Solid Dispersion from Solid-State NMR

Abstract: Despite the wide utilization of amorphous solid dispersions (ASDs) for formulating poorly water-soluble drugs, fundamental understanding of the structural basis behind their stability and dissolution behavior is limited. This is largely due to the lack of high-resolution structural tools for investigating multicomponent and amorphous systems in the solid state. In this study, we present what is likely the first publication quantifying the molecular interaction between the drug and polymer in ASDs at an angstro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 85 publications
0
52
0
Order By: Relevance
“…A detailed 13 C SS-NMR deconvolution study showed that binary KET and poly (acrylic acid) (PAA) system exhibits higher prevalence of ionic and hydrogen bonds in comparison with its ternary system containing hydroxypropyl methyl cellulose (HPMC) [60]. In recent studies, two-dimensional (2D) ss-NMR was also developed to identify the type and strength of various drug-polymer interactions in ASDs with enhanced sensitivity and resolution [61,62]. Lu et al used 2D 1 H- 19 F ss-NMR to investigate the molecular interaction between the difluorophenyl group of posaconazole and the hydroxyl group of hydroxypropyl methylcellulose acetate succinate (HPMCAS) in the ASD.…”
Section: Solid-state Nuclear Magnetic Resonance (Nmr)mentioning
confidence: 99%
See 1 more Smart Citation
“…A detailed 13 C SS-NMR deconvolution study showed that binary KET and poly (acrylic acid) (PAA) system exhibits higher prevalence of ionic and hydrogen bonds in comparison with its ternary system containing hydroxypropyl methyl cellulose (HPMC) [60]. In recent studies, two-dimensional (2D) ss-NMR was also developed to identify the type and strength of various drug-polymer interactions in ASDs with enhanced sensitivity and resolution [61,62]. Lu et al used 2D 1 H- 19 F ss-NMR to investigate the molecular interaction between the difluorophenyl group of posaconazole and the hydroxyl group of hydroxypropyl methylcellulose acetate succinate (HPMCAS) in the ASD.…”
Section: Solid-state Nuclear Magnetic Resonance (Nmr)mentioning
confidence: 99%
“…Lu et al used 2D 1 H- 19 F ss-NMR to investigate the molecular interaction between the difluorophenyl group of posaconazole and the hydroxyl group of hydroxypropyl methylcellulose acetate succinate (HPMCAS) in the ASD. For hydrogen bond patterns, they proposed that the hydroxyl groups of HPMCAS act as acceptors while the fluorine or difluorophenyl rings of posaconazole act as donors [62]. Moreover, a 19 F- 13 C rotational echo and double resonance technique was used to measure the atomic dis- In recent studies, two-dimensional (2D) ss-NMR was also developed to identify the type and strength of various drug-polymer interactions in ASDs with enhanced sensitivity and resolution [61,62].…”
Section: Solid-state Nuclear Magnetic Resonance (Nmr)mentioning
confidence: 99%
“…The values of m 1 determined separately for aprotic (1)(2)(3)(4)(5)(6)(7)(8)(9) and protic (10-14) solvents, correlation coefficients and difference in the ground and excited state dipole moment (∆µ) obtained on the basis of McRae (MR), Bakhshiev (B), and Lippert and Mataga (LM) models are also summarized in Table 2.…”
Section: Determination Of the Changes In The Dipole Momentmentioning
confidence: 99%
“…To overcome these limitations, polymeric drug carriers are used in which the poorly soluble active substance is dispersed [4][5][6][7]. As was shown, the polymer can decrease the drug crystallization ability due to polymer-drug interactions (such as hydrogen bonding) by reducing drug mobility and limiting drug-drug molecular interactions [8][9][10]. Thus, intermolecular interactions between the drug and the polymer can improve the drug stability, and consequently its bioavailability.…”
Section: Introductionmentioning
confidence: 99%
“…It is a powerful structural probe, and has had many successes in solving chemical structures of active pharmaceutical ingredients (APIs), their polymorphic forms, [2][3][4][5][6][7][8][9] or of amorphous solid dispersions. 10,11 However, sometimes the active ingredient is present in low concentration (<mmol), and the inherently low sensitivity of SSNMR (due to the small difference in nuclear spin populations at ambient temperatures), prevents the acquisition of experiments in a timely manner.…”
Section: Introductionmentioning
confidence: 99%